2019
DOI: 10.5210/fm.v24i10.10130
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and subjective well-being: The mediating role of social networking sites

Abstract: Many studies have examined the separate impacts of social capital (bonding and bridging) and the use of social networking sites (SNSs) on subjective well-being (SWB). However, few studies address the mediating role that SNS use has on the relationship between social capital and SWB. The current study addresses this research gap, examining the extent to which SNS use mediates the relationship between social capital and SWB. Moreover, this study theorizes SNS use to be a behavioural outcome of social capital, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…It was both the offline and online bonding social capital that predicted reduced perceived stress (not just the offline ones), though through different pathways; online bonding directly predicted reduced perceived stress for the whole sample and for men, whereas offline bonding indirectly, through resilience and life satisfaction. A stronger direct effect of bonding social capital than the indirect effect on subjective well‐being was also found by Hwang, Ng, and Vaithilingam (2019). No matter what the reasons for resorting to online bonding could be (limited/insufficient offline communication, inadequate capacities to form offline relationships, shyness, difficulties in face‐to‐face self‐disclosure, need to promote social connectedness; Hurt et al, 2012), it seems that it is beneficial, for college students at least, for decreasing their daily life stress (Brailovskaia et al, 2019; Burke & Kraut, 2016; Zhang, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…It was both the offline and online bonding social capital that predicted reduced perceived stress (not just the offline ones), though through different pathways; online bonding directly predicted reduced perceived stress for the whole sample and for men, whereas offline bonding indirectly, through resilience and life satisfaction. A stronger direct effect of bonding social capital than the indirect effect on subjective well‐being was also found by Hwang, Ng, and Vaithilingam (2019). No matter what the reasons for resorting to online bonding could be (limited/insufficient offline communication, inadequate capacities to form offline relationships, shyness, difficulties in face‐to‐face self‐disclosure, need to promote social connectedness; Hurt et al, 2012), it seems that it is beneficial, for college students at least, for decreasing their daily life stress (Brailovskaia et al, 2019; Burke & Kraut, 2016; Zhang, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…This is important because people in need may appear to be quite different from potential helpers (e.g., Bloom, 2016;Singer, 2010;Zaki, 2019). Critically, this work aligns broadly with the concept of bridging social capital which suggests that it is possible that giving to people who are socio-demographically dissimilar may be emotionally rewarding (e.g., Frey, 2008;Helliwell & Putnam, 2004;Hwang et al, 2019;Putnam, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, there is good reason to suspect that helping people who are dissimilar to you might be particularly emotionally rewarding. Indeed, past work suggests that bridging social capital or establishing connections with people from heterogeneous groups (i.e., people who are socio-demographically different than you) can be valuable and rewarding for well-being and positive psychological functioning (e.g., Frey, 2008;Helliwell & Putnam, 2004;Hwang et al, 2019;Putnam, 2000). Thus, the present work offers an opportunity to examine how realworld prosociality programs impact children's psychological well-being and provides a first look at whether these benefits may be different when helping dissimilar others.…”
Section: Do Real-world Prosociality Programs Predict Greater Psychological Well-being In Kids?mentioning
confidence: 99%
“…This finding is consistent with those from empirical research that perceived social capital positively correlated with subjective well-being, 72 , 73 specifically in the contexts of family and social media (Hwang et al, 2019). 63 , 74 Wise utilization of social media by professional sports franchises on building up perceived social capital among spectators is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“… 72 , 73 Similarly, one study found a positive relationship between social capital and subjective well-being in social media. 74 Furthermore, two sub-dimensions of neighborhood connections as well as feelings of trust and safety were found to significantly mediate the association between sport participation and well-being. 75 Hence, Hypothesis 8 (H8) postulated that spectators’ perceived social capital would positively relate to their subjective well-being.…”
Section: Introductionmentioning
confidence: 90%